Multisystem Inflammatory Syndrome in American Indian/Alaska Native Children, March 2020–May 2022. Issue 4 (30th December 2022) - Bornstein, Ethan R.; Miller, Allison D.; Zambrano, Laura D.; Yousaf, Anna R.; Apostolou, Andria; Weiser, Thomas; Campbell, Angela P.
Abstract : We describe characteristics, clinical features and outcomes of multisystem inflammatory syndrome in children among American Indian and Alaska Native (AI/AN) persons compared with non-Hispanic white persons. AI/AN patients with multisystem inflammatory syndrome in children were younger, more often obese, and from areas of higher social vulnerability. A greater proportion of AI/AN patients had severe respiratory involvement and shock.